EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI JAGUNG MANIS (STUDI KASUS DI KELURAHAN KESIMAN KECAMATAN DENPASAR TIMUR) - Gaudensia Seru; Cening Kardi; Nyoman Yudiarini (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2017)
The purpose of this research is to know: (1) Effect of Seed Production Factor, urea fertilizer, ponska fertilizer, manure and labor in Kesiman Village, and (2) Efficient Use of Seed Production Factor, urea fertilizer, ponska fertilizer, manure, farm work at Kelurahan Kesiman Denpasar Timur. The research was conducted by survey / interview, in Kelurahan Kesiman, This location was chosen purposively (purponsive), whereas while the determination of respondents selected simple random sampling (Simple Random Sampling). The production function performed in this research is the